METODE DEMONSTRASI (BURHAN) DALAM FILSAFAT ISLAM - Nano Warno (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2021)
This paper aims to analyze Islamic philosophy's demonstration (burha>n). Demonstration (burha>n) is the method of all schools of Islamic philosophy from Peripatetic, Illumination to Wisdom Muta'aliyah. Without demonstration (burha>n), philosophy is no more extended philosophy and turns to the debate of theologians. The consistent peripatetic Islamic philosophy maintains this method of discovering (context of discovery) the propositions discussed in Islamic philosophy. Illumination philosophy then adds an intuitive approach. The Muta'aliyah Hikmah school also added another source: the Koran and witnessing (kasyaf). The purpose of the study is to describe the function of Burhan to epistemology and spirituality by using the general hermeneutic to the primary and secondary literature of Islamic philosophy books, especially the corpus of the Hikmah Muta'aliyah and neo peripatetic schools. The research framework is the position of reason, and the laws of thought are called logic, and the purpose of logic is an argument; analogy, syllogism, and induction. burha>n is a particular syllogism. The conclusion of the demonstration (burha>n) contains three layers of structure; foundations, problems, and subjects, and requires a foundation developed from various sciences.